2014
DOI: 10.1016/j.jval.2014.08.2302
|View full text |Cite
|
Sign up to set email alerts
|

Decision Analysis on the Cost-Effectiveness of Sequential Treatment Strategies for Patients with Chronic Myeloid Leukemia in the United States

Abstract: A639 ment regimens for chronic myeloid leukemia. If further research were funded, studies should examine a combination of natural history, treatment, and quality of life parameters, especially the effectiveness of first-line TKI treatment.Objectives: The first goal was to adapt an existing Austrian decision-analytic model for chronic myeloid leukemia (CML) treatment to the US-American health care context. Secondly, we updated the model with new data and further treatment strategies to identify the most effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[20] Additionally, the model was applied to the U.S. health care context. [21] Furthermore, the project team implemented a software tool for the electronic collection of QoL data (CHES -Computerbased Health Evaluation System) and conducted several QoL surveys at the University Hospital Innsbruck, which are currently being analyzed. The final step of the project is to adapt the model in order to analyze a more personalized approach to treatment decisions for CML patients.…”
Section: Effectiveness and Cost Effectiveness Of Sequential Treatmentmentioning
confidence: 99%
“…[20] Additionally, the model was applied to the U.S. health care context. [21] Furthermore, the project team implemented a software tool for the electronic collection of QoL data (CHES -Computerbased Health Evaluation System) and conducted several QoL surveys at the University Hospital Innsbruck, which are currently being analyzed. The final step of the project is to adapt the model in order to analyze a more personalized approach to treatment decisions for CML patients.…”
Section: Effectiveness and Cost Effectiveness Of Sequential Treatmentmentioning
confidence: 99%
“…The cost-effectiveness of CML treatment has been of particular interest for physicians and researchers in many countries. [8][9][10][11] As a solution to this problem, Padula et al compared the costeffectiveness of an "imatinib-first" approach, in which physicians start treatment with imatinib, switching to dasatinib or nilotinib only in cases of resistance or intolerance, to that of a "physician's choice" approach, in which they initiate treatment with any 1 of 3 TKIs. 8 Their Markov model analysis clearly showed that the imatinib-first approach was associated with lower cost but similar quality-adjusted life years (QALYs) compared with the physician's choice approach.…”
Section: Introductionmentioning
confidence: 99%